The Role of Language in Structuring Social Networks Following Market Integration in a Yucatec Maya Population - Padilla-Iglesias, Cecilia; Kramer, Karen L. (Frontiers in Psychology, 2021)
Language is the human universal mode of communication, and is dynamic and constantly in flux to accommodate user needs as individuals interface with the changing world around them. However, we know surprisingly little about how language responds to market integration, a pressing force affecting indigenous communities worldwide today. While models of culture change often emphasize the replacement of one language, trait or phenomena, with another following socioeconomic transitions, we present a more nuanced framework. We use demographic, economic, linguistic and social network data from a rural Maya community that spans a 27-year period and the transition to market integration. By adopting this multivariate approach to the acquisition and use of languages, we find that whilst the number of bilingual speakers has significantly increased over time, bilingualism appears to be stable rather than transitionary. We provide evidence that under conditions where indigenous and majority languages provide complementary social and economic payoffs to individuals and the community, both can be maintained. Our results indicate the possibility of predicting the circumstances under which indigenous language use is sustained and equally those under which they are at risk. More broadly, they point to the evolutionary dynamics that shaped the current distribution of the world’s linguistic diversity.